2018
DOI: 10.1103/physrevd.97.066028
|View full text |Cite
|
Sign up to set email alerts
|

Semiclassical energy of open Nambu-Goto strings

Abstract: We compute semiclassical corrections to the energy of rotating open Nambu-Goto strings with and without masses at the ends, using methods from quantum field theory on curved space-times.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…In [17] it was shown that the the asymptotic behavior of the four point amplitude that corresponds to this model is a universal leading order correction of the Veneziano amplitude. Various other aspects of the model were investigated in [18][19][20][21][22][23][24][25].…”
Section: Contents 1 Introductionmentioning
confidence: 99%
“…In [17] it was shown that the the asymptotic behavior of the four point amplitude that corresponds to this model is a universal leading order correction of the Veneziano amplitude. Various other aspects of the model were investigated in [18][19][20][21][22][23][24][25].…”
Section: Contents 1 Introductionmentioning
confidence: 99%
“…This is of particular importance when generalizing the framework to quantum field theory on curved spacetime as advocated and pioneered in [BF00, BFV03,HW02]. Since then, the pAQFT framework has been applied to a wide class of physical problems including quantization of a bosonic string [BRZ14,Zah16] and effective quantum gravity [BFR13]. However, as pointed out in [Sum12], up to now it has not been tested on an interacting model for which nonperturbative results exists.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, we draw attention to the sign of the term linear in τ in (28) compared to (27), which was introduced in order to have usual sign in (29). The same phenomenon occurs for the open string, and in fact also for an analogous semi-classical treatment of the hydrogen atom [7]. 3 Also L1,4 − L2,3 commutes with L1,2 + L3,4, but it generates re-parametrizations.…”
Section: Perturbations Of Classical Rotating Circular Stringsmentioning
confidence: 57%
“…Due to this seeming inconsistency in non-critical dimension, it seems desirable to verify (1) with other methods. The result for the open string, including a generalization to masses at the endpoints, was recently re-derived in [7] using a semi-classical approximation, i.e., by quantizing the perturbations around classical rotating string solutions, and using a local renormalization procedure to extract quantum corrections to the energy. Here, we perform the analogous analysis for closed strings, also verifying (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation